Conceptual Metaphors and Image Schemas in a News Entitled “Katy Perry and Taylor Swift Officially Bury the Hatchet”: A Cognitive Semantic Study - Aurelia Reza Hayuwardhani (English Department - University of Sultan Ageng Tirtayasa, 2019)
Metaphors in cognitive semantics play important roles as phenomena to be understood. Understanding them require elaboration of both semantics and cognition. A news entitled “Katy Perry and Taylor Swift officially bury the hatchet” is an object that is worth studying in the light of cognitive semantics, especially the metaphors employed. The metaphors are compiled and classified into their types. From the metaphors obtained, the image schemas employed to understand the metaphors are explicated. The discussion on it is attached to the explanation of the metaphorical expressions found in the news. The result shows that there are 11 (eleven) metaphorical expressions with their own classifications noted and different image schemas that background the meaning-making process of the metaphors. Finally, by relying upon the results of the analysis, it can be concluded that there are ways, signified by the implementation of image schemas, to understand metaphors.